1992
DOI: 10.3109/00952999208992833
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings of Patterns of Substance Abuse in Eating Disorder Patients

Abstract: 207Am J Drug Alcohol Abuse Downloaded from informahealthcare.com by McMaster University on 12/03/14For personal use only. 144: 1283-1287 (1 987).Am J Drug Alcohol Abuse Downloaded from informahealthcare.com by McMaster University on 12/03/14For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Whereas some BN sufferers appear to be quite free of major psychopathology, a sizable subgroup displays prominent disturbances of mood (Milos et al, 2003), anxiety (Kaye et al, 2004), substance abuse (Newman and Gold, 1992), and personality (Cassin & von Ranson, 2005;Steiger and Bruce, 2007), as well as comorbid adult attention-deficit/hyperactivity disorder (Surman et al, 2006). Such heterogeneity has inspired the belief that, in BN, psychopathological variations correspond to important differences as to etiological processes and, in turn, treatment needs (Westen and Harnden-Fischer, 2001;Steiger and Bruce, 2007;Steiger et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Whereas some BN sufferers appear to be quite free of major psychopathology, a sizable subgroup displays prominent disturbances of mood (Milos et al, 2003), anxiety (Kaye et al, 2004), substance abuse (Newman and Gold, 1992), and personality (Cassin & von Ranson, 2005;Steiger and Bruce, 2007), as well as comorbid adult attention-deficit/hyperactivity disorder (Surman et al, 2006). Such heterogeneity has inspired the belief that, in BN, psychopathological variations correspond to important differences as to etiological processes and, in turn, treatment needs (Westen and Harnden-Fischer, 2001;Steiger and Bruce, 2007;Steiger et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Clearly, there are both eating-disordered patients who may also have a substance abuse problem, as well as substance abusers who may also have an eating disorder (Bulik, 1987;Newman & Gold, 1992;Steiger, Leung, Puentes-Neuman, & Gottheil, 1992). Interestingly, the severity of compulsive eating, particularly the frequency of binge-eating episodes, has been shown to be significantly and positively correlated with personality disorder symptomology (Picot & Lilenfeld, 2003).…”
Section: Commonalitiesmentioning
confidence: 98%
“…95 Studies of dual diagnosis patients with SUDs and disordered eating have shown that the eating disorder generally preceded the SUD. 96,97,98,99 In a prospective 10-year study of 95 anorexia nervosa patients, Kaye and colleagues found that even when there was no history of SUD initially, at 10-years, 12% of the restrictors and 50% of the binging subtype patients had a new diagnosis of comorbid substance use. 100 …”
Section: Eating Disordersmentioning
confidence: 99%